2010
DOI: 10.1186/1743-422x-7-323
|View full text |Cite
|
Sign up to set email alerts
|

Myotoxicity of telbivudine in pre-existing muscle damage

Abstract: ObjectivesIt is unknown if telbivudine causes muscle damage only in patients with pre-existing muscle pathology.Case reportA 27 yo male of African origin received telbivudine for hepatitis B during 3 months. Three weeks after initiation of the drug he developed myalgia, and tiredness. Creatine-kinase increased from 278 U/l (n, <170 U/l) at baseline to 3243 U/l. Shortly after discontinuation of telbivudine muscle symptoms and hyper-CK-emia disappeared. The findings suggest that pre-existing muscle damage favore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 6 publications
0
15
0
Order By: Relevance
“…Myopathy, characterized by muscle pain, weakness, and elevated CK levels, was reported in two patients, which resolved after telbivudine was discontinued 12,17. Preliminary data in the GLOBE trial11 found that 9 (1.4%) patients had new onset of grade 3 or 4 CK elevations and 9 (1.4%) had myalgia or myositis between 104 and 156 weeks 11,15,19. The safety profile of telbivudine over three years was similar to that reported at two years in the GLOBE trial; most adverse effects were mild and transient in nature and no new safety signals were observed 20.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Myopathy, characterized by muscle pain, weakness, and elevated CK levels, was reported in two patients, which resolved after telbivudine was discontinued 12,17. Preliminary data in the GLOBE trial11 found that 9 (1.4%) patients had new onset of grade 3 or 4 CK elevations and 9 (1.4%) had myalgia or myositis between 104 and 156 weeks 11,15,19. The safety profile of telbivudine over three years was similar to that reported at two years in the GLOBE trial; most adverse effects were mild and transient in nature and no new safety signals were observed 20.…”
Section: Discussionmentioning
confidence: 68%
“…Xue-song Zhang et al retrospectively reviewed five patients,18 and reported adverse reactions of telbivudine. Myalgia accompanied by general weakness, was the most common adverse reaction and the limb skeletal muscles were affected most frequently 17,19. There were four cases with peripheral nervous system involvement, represented by numbness and neuralgia, and one case with cardiac arrhythmia 12,18.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, there are a few case reports of telbivudineinduced myopathy (3,6). To our knowledge, this is the first report in Turkey regarding telbivudine-related myopathy confirmed by EMG.…”
Section: Discussionmentioning
confidence: 73%
“…Nucleos(t)ide analogues have an important role in the treatment of CHB. Telbivudine is a new nucleoside analogue (2,3). Transient creatine kinase (CK) elevation and rarely myopathy have been reported in a few number of patients who were treated with telbivudine (3).…”
Section: Introductionmentioning
confidence: 99%